2014
DOI: 10.1097/sle.0b013e3182a2f05f
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Versus Box Laparoscopic Simulators in Trainee Selection and Aptitude Testing

Abstract: In a selection center scenario, testing with low-fidelity platforms appears to demonstrate greater validity. Outliers can be identified using low-fidelity simulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Nonetheless, these two tasks may not have been ideal for assessment whereas other tasks such as suturing or clip application may have been more discriminating across experience. However, similar to our results, other studies have shown inconsistent or no construct validity of virtual reality motion metrics . In fact, an early report found that the experienced participants performed poorer than novices, which was suggested to be because of lack of tactile feedback, which is one of the disadvantages of non‐haptic virtual reality models.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Nonetheless, these two tasks may not have been ideal for assessment whereas other tasks such as suturing or clip application may have been more discriminating across experience. However, similar to our results, other studies have shown inconsistent or no construct validity of virtual reality motion metrics . In fact, an early report found that the experienced participants performed poorer than novices, which was suggested to be because of lack of tactile feedback, which is one of the disadvantages of non‐haptic virtual reality models.…”
Section: Discussionsupporting
confidence: 73%
“…The lack of construct validity for virtual reality motion metrics was surprising as virtual reality models are highly validated training tools and the motion metrics also have shown construct validity for assessment . However, previous validation studies of the virtual reality trainer used in this study have shown conflicting results . Eriksen and Duffy et al demonstrated construct validity in virtual reality using eight different tasks, and all metrics showed significant difference between the experienced and inexperienced group.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Madan and Frantzides (2007) found the combination of laparoscopic VR and laparoscopic box trainers to be superior to either system used alone in their study on preclinical medical students without prior operative experience (88). By contrast, Hennessey and Hewett (2014) concluded that testing with the low-fidelity FLS box trainer appears to demonstrate greater validity than the high-fidelity Lapsim virtual reality laparoscopic simulator (89). Hamilton et al (2002) compared the impact of video trainer (VT) vs VR on surgical technical skills in the operating room during a laparoscopic cholecystectomy procedure with 19 second-year residents assessed before and after training sessions and found the operative performance to be improved only in the laparoscopic VR training group (90).…”
Section: Laparoscopic Virtual Reality Simulators Versus Laparoscopic mentioning
confidence: 99%